Can Better Law Be Married with Corrective Justice or Evil Laws? - Peari, Sagi (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
This article offers an innovative understanding of the better law approach to choice of law. Through addressing the terminological fallacies of traditional and contemporary choice of law literature, depicting the conceptual distinction between the two versions of better law, and making a link between the better law approach and two central notions of legal theory—corrective justice and evil laws—this article provides a comprehensive analysis of the nature of better law.